EFEKTIVITAS MODEL TEAMS GAMES TOURNAMENT TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Virgianti, Umi; Khamdun; Wawan Shokib Rondli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low learning motivation of fourth-grade students at SD 4 Temulus due to the learning model used being conventional. This study aims to determine the increase in student learning motivation after the implementation of the Teams Games Tournament (TGT) learning model. The study used a quantitative approach with a one-group pretest-posttest design. The subjects of the study were 15 fourth-grade students. Data were collected through interviews, observations, documentation, and tests, and analyzed using the N-Gain test. The N-Gain test conducted on 15 students after using the Teams Games Tournament (TGT) model showed an average score of 0.4848 with a standard deviation of 0.24563. This result is included in the moderate category. The N-Gain score of each student ranged from 0.11 to 1.00, or in percentage form between 11.11% to 100%, with an average of 48.48%. These results indicate that the implementation of the Teams Games Tournament model has a positive impact on increasing the learning enthusiasm of fourth-grade students in Pancasila Education learning. Thus, the Teams Games Tournament model can be considered quite effective in increasing students' learning motivation through fun, competitive, and cooperative learning methods.